A low level of dietary selenium has both beneficial and toxic effects and is protective against Cd-toxicity in the least killifish Heterandria formosa. (October 2016) - Xie, Lingtian; Wu, Xing; Chen, Hongxing; Dong, Wu; Cazan, Alfy Morales; Klerks, Paul L.
Abstract: As an essential element, selenium (Se) is beneficial at low levels yet toxic at high levels. The present study assessed the effects of dietary exposure to Se in the least killifish Heterandria formosa, and investigated how this exposure influences the effects of a subsequent exposure to cadmium (Cd). The fish were pre-exposed to an environmentally relevant concentration (2 μg g −1 dry wt) of dietary selenite (Se 4+ ) or seleno-l -methionine (Se-Met) for 10 d. The same fish were then exposed to 0.5 mg L −1 of Cd for 5 d. Both Se(IV) and Se-Met rapidly accumulated in H. formosa . Results for the two Se species were generally similar in this study. Fish exposed to Se had lower levels of lipid peroxidation (measured as levels of thiobarbituric acid reactive substances or TBARS) and a higher catalase (CAT) activity. In contrast, their Na + /K + -ATPase activity was reduced. The Cd exposure resulted in an increase in lipid peroxidation and decreases in the activities of catalase and Na + /K + -ATPase. The Cd-exposed H. formosa that were pre-exposed to Se had lower Cd body burdens, less lipid peroxidation, and higher catalase activity, than did fish not pre-exposed to Se. The Se exposure did not have a protective effect on the Cd-induced reduction in Na + /K + -ATPase activity. These results clearly demonstrate that a Se-enriched diet reduces some (but not all) forms of Cd-toxicity and that Se can simultaneously have beneficial and detrimental effects, making it difficult to predict the net outcome of changes in dietary Se levels for fish. Highlights: The accumulation of Se in fish is mainly from the dietary route. Low level of Se exposure has detrimental effects on fish. The toxicity of Cd in Heterandria formosa could be reduced by Se pre-exposure. The protective role of Se on Cd exposure in fish deserves further studies.